The global prevalence of dental healthcare needs and unmet dental needs among adolescents: a systematic review and meta-analysis - Mahin Ghafari; Samira Bahadivand-Chegini; Tayebeh Nadi; Amin Doosti-Irani (Epidemiology and Health, 2019)
OBJECTIVES Access to dental healthcare services is a major determinant of dental health in communities. This meta-analysis was conducted to estimate the global prevalence of dental needs and of unmet dental needs in adolescents. METHODS PubMed, Web of Science, and Scopus were searched in June 2018. The summary measures included the prevalence of met and unmet dental needs. A meta-analysis was performed using the inverse variance method to obtain pooled summary measures. Out of 41,661 retrieved articles, 57 were ultimately included. RESULTS The pooled prevalence of orthodontic treatment needs was 46.0% (95% confidence interval [CI], 38.0 to 53.0), that of general treatment needs was 59.0% (95% CI, 42.0 to 75.0), that of periodontal treatment needs was 71.0% (95% CI, 46.0 to 96.0), and that of malocclusion treatment needs was 39.0% (95% CI, 28.0 to 50.0). The pooled prevalence of unmet dental needs was 34.0% (95% CI, 27.0 to 40.0). CONCLUSIONS The highest and lowest prevalence of unmet dental needs were found in Southeast Asia and Europe, respectively. The prevalence of dental needs was higher in the countries of the Americas and Europe than in other World Health Organization (WHO) regions. The prevalence of unmet dental needs was higher in Southeast Asia and Africa than in other WHO regions.